2001
DOI: 10.1021/ma000028v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interfacial Interactions on the Glass Transition of Polymer Thin Films

Abstract: Previous studies had demonstrated that the Tg of polymer thin films is strongly dependent on the interactions, γs, between the polymer and the underlying substrate. We present a study of the glass transition temperature, Tg, in thin films of polystyrene, PS, as a function of film thickness and as a function of γs by measuring the change in the thermal expansion using X-ray reflectivity. The Tg for PS on native silicon oxide was found to decrease with decreasing film thickness, consistent with results by others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
289
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(318 citation statements)
references
References 33 publications
26
289
1
2
Order By: Relevance
“…Plots of T 0 as a function of film thickness for PS films on both kinds of substrates are displayed in Figure 3. The general trend of the thickness dependence of T 0 shown for PS films on SiO 2 is consistent with the T g 's of similar films found by ellipsometry 19,20 and X-ray reflectivity 21 and a recent optical retardation study of PS on glass. 9 In particular, good quantitative agreement between the change in T g 19 and the change in T 0 as the PS film thickness is decreased from 50 to 10 nm supports the viewpoint that T 0 is directly related to T g .…”
Section: Resultssupporting
confidence: 88%
“…Plots of T 0 as a function of film thickness for PS films on both kinds of substrates are displayed in Figure 3. The general trend of the thickness dependence of T 0 shown for PS films on SiO 2 is consistent with the T g 's of similar films found by ellipsometry 19,20 and X-ray reflectivity 21 and a recent optical retardation study of PS on glass. 9 In particular, good quantitative agreement between the change in T g 19 and the change in T 0 as the PS film thickness is decreased from 50 to 10 nm supports the viewpoint that T 0 is directly related to T g .…”
Section: Resultssupporting
confidence: 88%
“…13 On the other hand, freely standing films appear to have a strong dependence on the molecular weight above approximately 500,000 g/mol, and T g decreases linearly with the film thickness for thicknesses below a molecular-weight-dependent critical value. 9,10 It is clear that free surface and interface effects are important factors in determining the magnitude and direction of changes in T g in polymer thin films; [5][6][7][8][9][10][13][14][15][16][17][18][19]40,41 however, the details of these effects are often contradictory or disputed, and a full understanding remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the interaction between a polymer and a solid substrate can suppress molecular relaxation in an interfacial region, leading to peculiar slower dynamics in this region. [9][10][11][12][13] Measurements of the relaxation rate using a 20-nm-thick fluorescently labeled layer that has been incorporated into polymer films have revealed that the rate of dynamics depends on the distance from both the free surface and the interface. These dynamics vary continuously, exhibiting bulk-like characteristics toward the interior layer sandwiched between the surface and the interfacial layers.…”
mentioning
confidence: 99%